CuSOD enzyme activity, partial purification from patients with diabetes type 1 - Qahtan Salman, Saif (Al-Qadisiyah Journal of Pure Science, 2018)
Antioxidants are agents that prevent or reduce the level of oxidative damage to biomolecules in the living organisms. Antioxidants can be enzymatic or non-enzymatic. An enzymatic antioxidants such as catalase, superoxide dismutase (SOD), and glutathione peroxidase (GPx) predominantly have metal chelators. Cu/Zn SOD enzyme, reacts with superoxide radical to form H2O2, which will get converted to H2O. In this study, (Cu)SOD was isolated from human RBCs using DEAE-cellulose chromatography. The enzyme was purified from patients with diabetes type 1 and normal people as well .The (Cu)SOD activity was measured in the serum of 20 samples of patients with diabetes and 20 normal samples